"Why can't I Have the Office Jobs?": Immigrant Latinx Transgender Peoples' Experiences with Seeking Employment. (February 2023) - Abreu, Roberto L.; Gonzalez, Kirsten A.; Lindley, Louis; Capielo Rosario, Cristalís; Lockett, Gabriel M.; Teran, Manuel
Research has documented the experiences of transgender people in seeking employment. To date, no scholarship has explored the experiences of immigrant Latinx transgender people seeking employment in the United States. Using an intersectionality framework, the present study aimed to uncover the experiences of immigrant Latinx transgender people as they sought employment in the United States. A community sample of 18 immigrant Latinx transgender people from a large metropolitan city in Florida engaged in semi-structured interviews. Thematic analysis revealed five themes related to participants' experiences seeking employment, including: (1) discrimination, (2) limited options, (3) positive experiences, (4) momentary de-transition, and (5) disability benefits as financial relief. Future directions such as exploring ways in which immigrant Latinx transgender people resist discrimination while seeking job opportunities are discussed. Implications for practice and advocacy such as advocating for equitable employment policies that acknowledge the intersectional experiences of this community are presented.